On the benefits of speech and touch interaction with communication services for mobility impaired users - Pires, C. G.; Pinto, F. M.; Rodrigues, E. M.; Dias, M. S. (Proceedings of the 1st International Living Usability Lab Workshop on AAL Latest Solutions, Trends and Applications - AAL, (BIOSTEC 2011), 2011)
Although technology for communication has evolved tremendously over the past decades, mobility impaired individuals still face many difficulties interacting with communication services, either due to HCI issues or intrinsic design problems with the services. In this paper we present the results of a usability study, conducted with a group of five mobility impaired users, comprising paraplegic and quadriplegic individuals. The study participants carried out a set of tasks with a multimodal (speech, touch, gesture, keyboard and mouse) and multiplatform (mobile, desktop) prototype, offering an integrated access to communication and entertainment services, such as email, agenda, conferencing and social media. The prototype was designed to take into account the requirements captured from these users, with the objective of evaluating if the use of multimodal interfaces for communication and social media services, could improve the interaction with such services. Our study revealed that a multimodal prototype system, offering natural interaction modalities, especially supporting speech and touch, can in fact improve access to the presented services, contributing to a better social inclusion of mobility impaired individuals.